1970
DOI: 10.3329/jard.v6i1.1660
|View full text |Cite
|
Sign up to set email alerts
|

Effect of N P K S Zn and B on Yield Attributes and Yield of French Bean in South Eastern Hilly Region of Bangladesh

Abstract: A field experiment on French bean taking the variety BARI Jhar Shim-2 was conducted with five levels of Nitrogen (0, 40, 80, ) and four levels of each of phosphorous (0, 40, 80 and 120

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 1 publication
12
15
0
Order By: Relevance
“…Compiling results from the greenhouse and field experiments published during 10 years, Guertal (2004) and Ross et al (2006) suggested that a level of 66 mg kg (1 in plant-leaf tissue is critical for B in lucerne. An increase in tissue N, P, K, Mg, Fe, and Mn upon B application was consistent with increases in P content for french bean (Phaseolus vulgaris L.) (Moniruzzamen et al, 2008), K content of lentils (Lens culinaris Medikus) (Singh & Singh, 1983), Zn content of sugar beet (Beta vulgaris L.) (Hamurcu & Gezgin, 2001), Fe content of rice (Oryza sativa L.) (Santra et al, 1989), and Mn content of cowpeas (Vigna unguiculata) (Singh, 1988). McKenzie (1992McKenzie ( & 2005 defined critical ranges of 3.0Á5.0% for N, 0.2Á0.70% for P, 1.7Á3.80% for K, 0.25Á3.00% for Ca, 0.2Á1.0% for Mg, 5Á30 mg kg (1 for Cu, 20Á250 mg kg (1 for Fe, 20Á200 mg kg (1 for Mn, and 20Á70 mg kg (1 for Zn for the upper 15 cm of lucerne at the 10% bloom stage.…”
Section: Discussionsupporting
confidence: 67%
“…Compiling results from the greenhouse and field experiments published during 10 years, Guertal (2004) and Ross et al (2006) suggested that a level of 66 mg kg (1 in plant-leaf tissue is critical for B in lucerne. An increase in tissue N, P, K, Mg, Fe, and Mn upon B application was consistent with increases in P content for french bean (Phaseolus vulgaris L.) (Moniruzzamen et al, 2008), K content of lentils (Lens culinaris Medikus) (Singh & Singh, 1983), Zn content of sugar beet (Beta vulgaris L.) (Hamurcu & Gezgin, 2001), Fe content of rice (Oryza sativa L.) (Santra et al, 1989), and Mn content of cowpeas (Vigna unguiculata) (Singh, 1988). McKenzie (1992McKenzie ( & 2005 defined critical ranges of 3.0Á5.0% for N, 0.2Á0.70% for P, 1.7Á3.80% for K, 0.25Á3.00% for Ca, 0.2Á1.0% for Mg, 5Á30 mg kg (1 for Cu, 20Á250 mg kg (1 for Fe, 20Á200 mg kg (1 for Mn, and 20Á70 mg kg (1 for Zn for the upper 15 cm of lucerne at the 10% bloom stage.…”
Section: Discussionsupporting
confidence: 67%
“…2). Moniruzzaman et al (2008) mentioned similar trend in combination effect of different levels of fertilizers. Application of N 120, P 80, K 60, S 20, Zn 4 and B 1kg ha-1recorded the highest number of green pods per plant of French bean.…”
Section: Number Of Fruits Per Bunchmentioning
confidence: 88%
“…Feng et al, (2017) working on potato found that the highest tuber yield was 38.0 Mg ha-1 for 90% NPK. Moniruzzaman (2008) reported that the highest pod yield of 23.14t ha-1 was obtained with 120-120-60-20-4-1 kg of N-P2O5-K2O-SZn-B plus 0.5 kg Mo ha-1 on French bean. Applications of 140 or 80 kg nitrogen ha-1 at sowing alongside applications of 20 kg sulphur ha-1 resulted into higher yield of wheat (Hayat et al, 2015).…”
Section: Yield Per Palmmentioning
confidence: 99%
“…This result is in full agreement with Singh et al (2009) who reported that higher number of pods plant -1 was in 180 kg ha -1 N application. Moniruzzaman et al (2008) also reported that there was a significant effect of N fertilizers on pods production plant -1 whereas the maximum pods plant -1 was obtained with 120-120-60-20-4-1 kg of N-P 2 O 5 -K 2 O-SZn-B.Parvez (2011) also found that high N dose (50 kg ha -1 ) gave significantly higher number of pods and seeds pod -1 .…”
Section: Effect Of Rate Of Nitrogenmentioning
confidence: 92%